2014
DOI: 10.1111/eth.12286
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Lines of Egg Defense in a Neotropical Arachnid with Temporary Brood Desertion

Abstract: Egg predation is the one of the main costs of brood desertion in many ectothermic animals. When stressful environmental conditions constrain parental activities to only some periods of the day, the combination of physical or chemical defenses may attenuate the costs related to egg loss during periods of temporary parental absence. Females of the harvestman Neosadocus maximus periodically abandon their clutches to shelter or forage. They also cover their eggs with a hygroscopic mucus coat and seem to lose fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Zink, ; Requena et al , ; Chelini & Machado, ). Indeed, a recent study on a clade of Neotropical harvestmen has shown a strong correlation between the presence of additional defences (mucus or debris egg coating) with temporary or permanent parental abandonment of eggs (Chelini & Machado, ). It would be worthwhile to investigate the order in which these two traits have evolved to test whether additional defences are a cause or a consequence of offspring abandonment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zink, ; Requena et al , ; Chelini & Machado, ). Indeed, a recent study on a clade of Neotropical harvestmen has shown a strong correlation between the presence of additional defences (mucus or debris egg coating) with temporary or permanent parental abandonment of eggs (Chelini & Machado, ). It would be worthwhile to investigate the order in which these two traits have evolved to test whether additional defences are a cause or a consequence of offspring abandonment.…”
Section: Discussionmentioning
confidence: 99%
“…); egg coating with mucus in harvestmen (e.g. Requena et al , ; Chelini & Machado, ; Fig. ); egg covering with debris and silk in webspinners (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Neosadocus maximus : Kury, 1995: 205 [ 18 ] (diag; dist); 2003: 135 [ 2 ] (cat); Osses et al, 2008: 519, 520, 522, figs 1–2, 523, figs 4–5, 524, 525 [ 9 ] (biol); Willemart et al, 2009: 52, 53, 54, figs 1–2, 55, figs 3–4, 56, fig 5, 57, 58 [ 10 ] (biol); Rocha et al, 2011: 658, 659, 660, fig 4, 661, figs 5–5b [ 67 ] (biol); Resende et al, 2012: 101, 102 [ 6 ] (cit); Chelini & Machado, 2012: 1620, fig 1, 1621, 1622, 1623, fig 2, 1624, fig 3, 1625, 1626 [ 12 ] (biol); 2014: 1148, 1149, 1150, fig 1, 1151, fig 2, 1152 [ 68 ] (biol); Buzatto & Machado, 2014: 4 [ 69 ] (cit); Buzatto et al, 2014: 1681 [ 70 ] (biol; cit); Pinto-da-Rocha et al, 2014: 522, 534 [ 46 ] (syst); Benedetti & Pinto-da-Rocha, 2019: 462, 466, 467, 468, 469, 470 [ 58 ] (mat; syst).…”
Section: Resultsmentioning
confidence: 99%
“…Neosadocus maximus : Kury, 1995: 205 [15]; 2003: 135 [2]; Osses et al, 2008: 519, 520, 522, figs 1–2, 523, figs 4–5, 524, 525 [9]; Willemart et al, 2009: 52, 53, 54, figs 1–2, 55, figs 3–4, 56, fig 5, 57, 58 [10]; Rocha et al, 2011: 658, 659, 660, fig 4, 661, figs 5–5b [65]; Resende et al, 2012: 101, 102 [6]; Chelini & Machado, 2012: 1620, fig 1, 1621, 1622, 1623, fig 2, 1624, fig 3, 1625, 1626 [12]; 2014: 1148, 1149, 1150, fig 1, 1151, fig 2, 1152 [66]; Buzatto & Machado, 2014: 4 [67]; Buzatto et al, 2014: 1681 [68]; Pinto-da-Rocha et al, 2014: 522, 534 [42]; Benedetti & Pinto-da-Rocha, 2019: 462, 466, 467, 468, 469, 470 [54].…”
Section: Resultsmentioning
confidence: 99%